ДОСЛІДЖЕННЯ ВПЛИВУ ДІВЕ-ОБРОБКИ ПЛОДОВОГО ТІЛА ГРИБА ШИЇТАКЕ НА ФІЗИКО-МЕХАНІЧНІ ВЛАСТИВОСТІ ГРИБНОЇ СУСПЕНЗІЇ - Sharkova, N.O.; Zhukotskyi, E.К.; Тurchyna, Т.Y.; Dekusha, H.V.; Makarenko, A.A. (Institute of Engineering Thermophysics of NAS of Ukraine, 2018)
The use of discrete-pulse energy input (DPEI) mechanisms in various industries has become a reliable tool for the intensification of heat and mass transfer processes in various technological lines and reduction of specific energy consumption. The study of structural transformations in heterogeneous systems under influence of mechanisms of DPEI opens up new possibilities for their use as evidenced by this article. Under certain conditions it is possible to prepare a mushroom suspension with specified characteristics for drying and enhance medicinal properties of the obtained powder product while retaining all valuable components of feedstock. The article presents the results of research of DPEI-processing effect of the shiitake mushroom fruit body on the on physical and mechanical properties and structural characteristics of the mushroom suspension. The influence of hydro module, temperature of the suspension and the layout of the working bodies of the rotor-pulse apparatus (RPA) on its dynamic viscosity was studied and the possibility of reducing viscosity by 2-3 times is shown.  An analysis of mushroom suspension microstructure has showed that with a certain layout of the working bodies of the RPA it is possible to control the degree of dispersion of particles and change the spatial structure of the aggregates in the volume of the dispersion medium. It is determined that self-organization of spatial aggregates from individual hyphae in such suspensions occurs over time. Moreover, the smaller the size of hyphae (≤ 25 microns after the RPA of the first version of the arrangement: rotor-stator-rotor) are, the larger the size of the spatial aggregates are formed. After the RPA with the second layout option, the fragments of hyphae had sizes ≥ 50 μm, but the dimensions of the spatial aggregates were three times smaller. It is found that after three times passing of the mushroom suspension through the RPA and its subsequent treatment in the cavitation device, the dynamic viscosity of the suspension is reduced by 20%. Confirmation of the the effectiveness of the DPEI-mechanisms in obtaining mushroom suspension is that due to the hydromechanical destruction of the polysaccharide structures of the chitin-glucan complex of the shiitake mushroom the content of the bioavailable complex of water-soluble oncostatic and immunoregulatory polysaccharides in the powder obtained by drying the mushroom suspension in an experimental spray dryer increased 6 times. References 13, figures 6.